Optimizing Surgical Site Infection Prediction Performance Through a Combined Approach of SMOTE-ENN, SMOTE-Tomek, and Wrapper Feature Selection - Al-Ahmari, Salha (Communications in Mathematics and Applications, 2025)
Risk stratification can be enhanced by assessing preoperative risk factors, which are essential for guiding surgical decision-making. Machine learning (ML) and AI-based expert systems can predict, detect, and monitor surgical site infections (SSIs) using data from electronic healthcare records (EHRs). The predictive capability of classification algorithms is impaired by class imbalance and depends heavily on the quality of features in a dataset, which may include irrelevant or redundant information. The primary goal of feature selection is to remove such features to improve classification accuracy. This study utilized a dataset of 64,793 surgical records, each featuring 25 variables, to evaluate six machine learning classification methods: logistic regression (LR), K-Nearest Neighbors(KNN), decision tree classifier (DTC), support vector machine (SVM), Gaussian Naive Bayes (GNB), and artificial neural network (ANN). These techniques, intended to enhance classification accuracy, frequently prioritize the majority class in an imbalanced dataset, hence distorting the accuracy metric. To address the imbalanced classification problem in SSI prediction. The study applied the hybrid sampling techniques SMOTEMOTE-ENN and SMOTE-Tomek, combined with wrapper feature selection, to improve the model performance. The wrapper feature selection model optimizes the feature set by reducing the number of features while simultaneously enhancing the classification accuracy. Findings represented that the combined sampling of Edited Nearest Neighbors and SyntheticMinority Oversampling Technique (SMOTE-ENN) with wrapper feature selection outperformed the SMOTE-Tomek in all performance metrics (KNN; AUC: 98, recall: 61, precision: 80, F1-score: 69, and accuracy: 98) and (DTC; AUC: 93, recall: 60, precision: 76, F1-score: 67, and accuracy: 98), particularly for minority class. When paired with SMOTE-ENN sampling and optimized through wrapper feature selection, the SSI prediction accuracy and AUC were significantly enhanced. The proposed method effectively mitigates the overfitting and underfitting issues, though the wrapper method is computationally intensive, which results in longer training times.
Keywords: Imbalanced classification; Combined sampling; Surgical site infection; Machine learning; Wrapper feature selection